Edukasi Protokol Kesehatan Rumah Sakit - Novita Dewi; Supriyadi Supriyadi (Jurnal Abdimas Kesehatan (JAK), 2022)
Corona virus infection, also known as COVID-19 (Corona Virus Disease 2019), is booming, spreading rapidly, resulting in death. Prevention of the spread of the virus by implementing health protocols carried out by all aspects of society, especially in hospitals, where patients are cared for and the families who look after them, are very vulnerable to contracting COVID-19, so education is needed for the patient's family about the health protocol. The implementation of health protocols can be improved through education on the implementation of health protocols carried out in hospitals. The purpose of community service is to provide education to the families of patients who are hospitalized. The method used is the CBR (Community Based Research) approach, by educating the patient's family directly/offline one by one by implementing health protocols; wear a mask, keep your distance, avoid crowds. The time for the education implementation on December 28, 2020, was carried out on the patient's family with a duration of 20 minutes. Community service is carried out with a community service team consisting of professional students for the 2020/2021 academic year. The media used in the form of leaflets. The results of community service in the form of increased knowledge and changes in the implementation of health protocols. Knowledge is obtained, all of the patient's family understands the material for implementing the health protocol that has been given. Recommendations for community service in the future use interactive learning media so that the education provided can be understood properly.